2006
DOI: 10.1097/01.tp.0000200307.79962.48
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Determination of Pharmacokinetics and Pharmacodynamics of Mycophenolic Acid in Liver Transplant Patients Treated with Mycophenolate Mofetil

Abstract: During the first postoperative months, exposure to MPA is low in a considerable proportion of liver transplant patients receiving MMF at a fixed dose of 1 g bid. MPA monitoring appears necessary in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 26 publications
(29 reference statements)
5
30
0
Order By: Relevance
“…185,188 Hepatic UGT2B7 is the main enzyme involved in the formation of the quantitatively less important but pharmacologically active acyl-glucuronide of MPA (AcMPAG). 188 UGT1A7, UGT1A8, and UGT1A10 expressed in the gastrointestinal tract and the kidney play a minor role in both MPAG and AcMPAG 134 Shaw et al, 135 van Hest et al, 136 Gonzalez-Roncero et al, 137 Kaplan et al, 138 Johnson et al 139 136 Atcheson et al, 143 Atcheson et al, 144 Jain et al, 145 128 Weber et al, 131 Oellerich et al, 132 Kuypers et al, 133 Borrows et al, 142 Jain et al, 145 Cattaneo et al, 149 Brunet et al, 150 Cattaneo et al, 151 formation. 188 Importantly, both MPA and MPAG are extensively bound to serum albumin with a mean albumin binding of 97% and 82%, respectively.…”
Section: Mpa: Basic Principles Of Pharmacodynamics and Pharmacokineticsmentioning
confidence: 97%
“…185,188 Hepatic UGT2B7 is the main enzyme involved in the formation of the quantitatively less important but pharmacologically active acyl-glucuronide of MPA (AcMPAG). 188 UGT1A7, UGT1A8, and UGT1A10 expressed in the gastrointestinal tract and the kidney play a minor role in both MPAG and AcMPAG 134 Shaw et al, 135 van Hest et al, 136 Gonzalez-Roncero et al, 137 Kaplan et al, 138 Johnson et al 139 136 Atcheson et al, 143 Atcheson et al, 144 Jain et al, 145 128 Weber et al, 131 Oellerich et al, 132 Kuypers et al, 133 Borrows et al, 142 Jain et al, 145 Cattaneo et al, 149 Brunet et al, 150 Cattaneo et al, 151 formation. 188 Importantly, both MPA and MPAG are extensively bound to serum albumin with a mean albumin binding of 97% and 82%, respectively.…”
Section: Mpa: Basic Principles Of Pharmacodynamics and Pharmacokineticsmentioning
confidence: 97%
“…This resulted in death in two patients and required retransplantation in one patient [67]. In all studies using MPA monotherapy, there was no pharmacological monitoring of mycophenolic acid (the active form of MPA) blood levels, although significant inter-individual and intra-individual variability in the pharmacokinetics is well established [68].…”
Section: Cni Withdrawalmentioning
confidence: 99%
“…MPA monotherapy after CNI withdrawal is considered too risky due to a 12-15% risk of rejection, but safety could be improved by pharmacological monitoring of MPA [68], an approach which is currently under investigation [92].…”
Section: Cni Withdrawalmentioning
confidence: 99%
“…A recent study reported that in liver transplant patients, the consistent pharmacologic activity of MPA was shown from patients' sera only when MPA AUC or predose concentration was within the recommended range listed previously (49). Also, in kidney transplant patients who were on CsA-based therapy, MPA AUC on day 3 was predictive of later incidence of acute rejection (P ϭ 0.007) (50), suggesting the importance of adequate MPA exposure, as early as posttrans- plantation day 3, for prevention of acute rejection.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%